Knee and hip joints endoprothesis in old and senile patients with rheumatic diseases - V P Pavlov; G N Vardikova. S.A; G N Makarov; G. A. Matushevsky; М А Макаров; G F Nasarenko (Научно-практическая ревматология, 2003)
Knee and hip joint endoprothesis (EP) outcomes were studied in 40 old and senile pts (mean 67,3 years) with rheumatic diseases in comparison to 101 pts of young and middle age (mean 42,7 years). Risk in EP of larege joints was determined by the presence and severity of concomitant diseases, mainly by cardiovascular and respiratory diseases. Mortality in old group achieved 6% in comparison with 1% in pts of young and middle age. Fatal outcome was noted in pts with history of coronary heart disease and myocardial infarction as well as in pts with chronic respiratory diseases. The following data were described: long-term results of knee and hip joints EP, quality of life assessment, functional assessment of operated joints according to HAQ, Harris, Insall and Wallly criteria.